Satisfação e lealdade dos estudantes que frequentam os cursos técnicos superiores profissionais: o caso do Instituto Politécnico de Bragança - Ferreira, Inês S. (2017)
The main objective of the present empirical research is to analyse the satisfaction and loyalty of students who attend the Professional Technical Higher Courses (CTeSP) at the Polytechnic Institute of Bragança. This study adopted a quantitative approach through the application of a survey to students from CTeSP. Surveys were applied to the 370 students enrolled in these courses, with a final sample error of 3.1% and a significance level of 5%. It was confirmed the existence of a positive association between the variables “relation of the CTeSP with the Polytechnic Institute of Bragança” and “Global Satisfaction” and the variables “would recommend the Polytechnic Institute of Bragança to a friend”, “intends to continue its course in the Polytechnic Institute of Bragança” and “Global Satisfaction”, this means that they are related, one variable depends on the other. Finally, it was verified that there is no association between the “residence at the date of application in the Polytechnic Institute of Bragança” and the “CTeSP that attends”, that is to say there is no relation between these variables, since the students do not choose the CTeSP that they attend taking into account the residence they had at the time of application.